2005
DOI: 10.1111/j.1742-6723.2005.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian torsion: 10‐year perspective

Abstract: The diagnosis of ovarian torsion remains challenging. Clinical characteristics lack sensitivity and specificity and ultrasound diagnosis is not definitive. Laparoscopy remains the investigation of choice. Despite delays in diagnosis this study demonstrates relatively high ovarian salvage rates compared with most published data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 24 publications
8
111
1
9
Order By: Relevance
“…Se ha observado, del punto de vista funcional, después de una destorsión, que estos ovarios muestran desarrollo folicular y respuesta adecuada frente a su estimulación farmacológica, con fertilización oocitaria en procedimientos posteriores de fertilización in vitro. En concordancia con lo expuesto, diversas revisiones demuestran que a pesar de existir un retraso en el diagnóstico y tratamiento, las tasas de preservación de la función ovárica pueden ser altas (38). Otro elemento a favor de la destorsión ovárica es que en la literatura médica no hay informes de un incremento en el riesgo de eventos tromboembóli-cos.…”
Section: Discussionunclassified
“…Se ha observado, del punto de vista funcional, después de una destorsión, que estos ovarios muestran desarrollo folicular y respuesta adecuada frente a su estimulación farmacológica, con fertilización oocitaria en procedimientos posteriores de fertilización in vitro. En concordancia con lo expuesto, diversas revisiones demuestran que a pesar de existir un retraso en el diagnóstico y tratamiento, las tasas de preservación de la función ovárica pueden ser altas (38). Otro elemento a favor de la destorsión ovárica es que en la literatura médica no hay informes de un incremento en el riesgo de eventos tromboembóli-cos.…”
Section: Discussionunclassified
“…Çoğu vakada torsiyona eşlik eden adneksiyel bir kitle bulunurken % 8-18 vakada ise patolojik bir kitle yoktur. Benign ovaryen patolojilerin çoğunluğunu ovaryen ve paraovaryen kistler oluşturur (2). Kistik teratomlar (% 60) ve kistadenomlar (% 30) torsiyonlarda en sık karşılaşılan iyi huylu tümörlerdendir (3).…”
Section: Introductionunclassified
“…In 2005, White M et al 18 conducted a retrospective study over a period of ten years and found fifty two cases of ovarian torsion. The main clinical features of presentation were sudden pain in 83% cases and nausea and vomiting in 59% cases.…”
Section: Ovarian Torsionmentioning
confidence: 99%
“…In 2005, White M et al 18 conducted a retrospective study over a period of 10 years and found fifty two cases of surgically proven ovarian torsion. The mean age of presentation was 33.5 years with interquartile range from 28.7 years to 39.3 years.…”
Section: Ovarian Torsionmentioning
confidence: 99%